Can concrescence diagnosis be obtained merely by clinical and imaging examination? from clinical case to histology (Research, Society and Development, 2020)
Concrescence is a rare type of union of two teeth, with no predisposition for a particular ethnicity, gender or age, specifically united by a portion of cementum, without the fusion of dentin, commonly reported in the posterior maxilla region, in most cases, this anomaly affects the second and third molars. Its diagnosis is suggested by radiographic images when there is proximity between two teeth, without signs of the periodontal ligament, or interdental bone between them, often showing a radiographic overlap. The lack of attention to these signs can lead to complications during endodontic and surgical procedures, such as unplanned extraction of the involved teeth, even leading to legal problems. The aim of this paper is to report a histologically proven case of concrescence between an erupted second molar largely compromised by caries and an impacted third molar, in addition to presenting a literature review, along with the histological aspect, about the subject.